2013
DOI: 10.5194/isprsarchives-xl-1-w2-401-2013
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Uas for Assessing Agricultural Systems in an Wetland in Tanzania in the Dry- And Wet-Season for Sustainable Agriculture and Providing Ground Truth for Terra-Sar X Data

Abstract: The paper describes the assessment of the vegetation and the land use systems of the Malinda Wetland in the Usambara Mountains in Tanzania with the parachute UAS (unmanned aerial system) SUSI 62. The area of investigation was around 8 km². In two campaigns, one in the wet season and one in the dry season, approximately 2600 aerial photos of the wetland were taken using the parachute UAS SUSI 62; of these images, ortho-photos with a spatial resolution of 20 cm x 20 cm, were computed with an advanced block bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A smaller group of studies (n = 8) in our pool applied UAVs towards developing generalizable methodologies for image processing, information extraction, and/or field surveying [6,76,78,[132][133][134]136,137] using RGB, RGB and Multispectral, and LiDAR sensors (Figure 3). Such studies often emphasized methodology-building efforts more than sitespecific ecological questions and discussed the relevance of the proposed analyses and workflows to wetland management, conservation, or research beyond their specific case study sites.…”
Section: Ground Reference Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A smaller group of studies (n = 8) in our pool applied UAVs towards developing generalizable methodologies for image processing, information extraction, and/or field surveying [6,76,78,[132][133][134]136,137] using RGB, RGB and Multispectral, and LiDAR sensors (Figure 3). Such studies often emphasized methodology-building efforts more than sitespecific ecological questions and discussed the relevance of the proposed analyses and workflows to wetland management, conservation, or research beyond their specific case study sites.…”
Section: Ground Reference Applicationsmentioning
confidence: 99%
“…Such studies often emphasized methodology-building efforts more than sitespecific ecological questions and discussed the relevance of the proposed analyses and workflows to wetland management, conservation, or research beyond their specific case study sites. Four of these applications focused on UAV data processing for mapping and quantitative assessments of vegetation [76,133,134] and hydrological properties [132], while four other studies concentrated primarily on UAV surveying workflows [6,136,137], with one study proposing a full workflow for both surveying and subsequent image processing for riverine and estuarine landscape change assessment [78].…”
Section: Ground Reference Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research studied the broader characteristic attributes of a wetland to meet the requirements of the wetland delineation (DWAF, 2008) and classification (Kotze et al, 2005). Existing UAV photogrammetry literature such as Li et al (2010), Thamm et al (2013), Marcaccio et al (2015) and Zweig et al (2015) mostly focussed on wetland vegetation classification. The findings of this study are comparable to the results of these studies in terms of identification and mapping of dominant wetland vegetation from the HROs although this research used products such as the 0.038 m point cloud and DEM in combination with the HROs to assist with the mapping which proved to be highly accurate.…”
Section: Wetland Delineation and Classificationmentioning
confidence: 99%
“…The results of this study indicated that the combination of two new technologies (UAV and object-based image analysis (OBIA) methods can successfully classify swamp vegetation extents. Thamm et al (2013) used a UAV to assess agricultural systems in a wetland in Tanzania in the wet and dry season over an area of 8 km 2 . A block bundle approach was used to compute the orthophotos and georeference the control points taken with a differential GPS.…”
Section: Introductionmentioning
confidence: 99%